THE IMPLICATIONS OF APPLYING SCIENTIFIC APPROACH IN ISLAMIC EDUCATION LEARNING - Shodiq, Sadam Fajar (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The Characteristics of Islamic Education (PAI) learning according the material given can not be explained scientifically. There are some learning materials that need only to be believed in as that the learning of the existence of God. This is contradictory with the approach used in PAI learning in the curriculum of 2013 that has been established that is scientific approach. Scientific approach requires scientific thinking, whereas some PAI materials cannot be explained scientifically. This research is a literary Research in which the researchers conduct Depp analysis of various written sources either from the results of research or books. The results showed that the characteristics of PAI learning is learning through the meaning of something that exists in the environment. Because the quality of life of students depends on how students interpret every life event happening to them. In interpreting a thing, it should be done in 3 ways, those are how students see, with what students see, and under the conditions of how students see. The scientific approach is an approach used in learning by emphasizing the use of scientific methods in teaching and learning activities. The implication of the implementation of a scientific approach in the learning process of PAI is using learning materials based on facts or phenomena that can be explained by certain logic or reasoning, rather than rely on assumption or speculation. The learning process should encourage and inspire students to think critically, analytically and appropriately in identifying, understanding, solving problems, and applying learning materials.